Assessment of the properties and environmental impact of carbonated reactive magnesia containing industrial waste - Ruan, Shaoqin (2023)
To achieve the goal of carbon neutrality, carbon capture and storage (CCS) is considered to be an effective approach. This study investigated the microstructural development of reactive magnesia cement-industrial waste (i.e., pulverized fly ash and ground granulated blast-furnace slag) formulations under accelerated carbonation conditions. The density and isothermal calorimetry analyses were supported with microstructural analysis performed. Results showed that pulverized fly ash and ground granulated blast-furnace slag could be activated by reactive magnesia cement, resulting in the formation of phases such as magnesia silicate hydrate, hydrotalcite and hydromagnesite, whose formation was enhanced in the presence of accelerated carbonation. Associated with a low initial pH, samples with pulverized fly ash outperformed samples with ground granulated blast-furnace slag counterparts in terms of their strength development. The study led to the determination of a formulation containing the reactive magnesia cement and pulverized fly ash with a higher mechanical performance than the control group, also highlighting the need for the revision of the adopted carbon footprint calculation to incorporate several critical factors.